Somos como las nubes = We are like the clouds - Argueta, Jorge (Groundwood Books, House of Anansi Press, 2016)
Why are young people leaving their country to walk to the United States to seek a new, safe home? Over 100,000 such children have left Central America. This book of poetry helps us to understand why and what it is like to be them.